KERAGAMAN AKTINOMISETES ASAL SERASAH, SEDIMEN, DAN TANAH PULAU ENGGANO, BENGKULU - Ade Lia Putri; Arif Nurkanto (Research Center for Biology-Indonesian Institute of Sciences, 2016)
A total of 344 isolates of actinomycetes were isolated from leaf litter and soil samples collected from four locations of Enggano Island, Bengkulu. eighty eight isolates were selected using morphological characteristics and identified using 16S rRNA gene sequence analysis. Three families (Micromonosporacea, Streptomycetaceae, and Streptosporangiaceae) and eight genera were found from these samples. Approximately 80% of these strains belonged to Streptomyces group and 20% of isolates were similar to rare actinomycetes. Based on homology search (BLAST) and phylogenetic tree analysis, isolates of rare actinomycetes (EgA15, EgA30, EgA85, EgA386, EgA236, EgA243, EgA335, EgA112, EgA41,EgA312, EgA314) were identified as Kitasatosporia paracochleata (100%), Kitasatospora azatica (99%), Kitasatospora griseola (99%), Sphaerisporangium album (99%), Actinoplanes nipponensis (99%), Pseudosporangium ferrugineum (99%), Nonomuraea rosela (99%), Nonomuraea guangzhouensis (98%), Micromonospora chaiyaphumensis (99%),Micromonospora chaiyaphumensis (99%), and Couchioplanes caeruleus (99%) respectively.